¹³⁷Cs circulation in forest ecosystems on the territory of the Chernobyl exclusion zone (Soil) - Zarubina, N.Ye. (Доповіді НАН України, 2020)
Seasonal changes in the content of ¹³⁷C in soils were studied at three forest ecosystems in the territory of the Chernobyl
exclusion zone. The soils were selected layer by layer: A₀l, A₀f+A₀h, 0-5 and 5-10 cm with the frequency
of once every two weeks during 2013-2015. Intermittent changes in the levels of the specific activity of ¹³⁷C in all
studied soil layers during the calendar year were recorded at the sites. The dependences of the content of ¹³⁷C in
different soil layers on the season of the year have not been identified. The calculation of correlation coeffi cients
indicates the existence of a relationship between fluctuations in the concentration of radiocaesium only between
layers of 0-5 and 5-10 cm. Air temperature and precipitation over different time intervals preceding the sampling do
not affect the redistribution of ¹³⁷C in the soil of the forest ecosystems. It has been suggested that the absence of
seasonal patterns of changes in the content of ¹³⁷C in soils is associated with its heterogeneity (different amounts of
soil biota in each sample). Сезонні зміни вмісту ¹³⁷C у ґрунтах вивчались у трьох лісових екосистемах на території Чорнобильської
зони відчуження. Ґрунти відбирали пошарово: A₀l, A₀f + A₀h, 0—5 та 5—10 см з частотою один раз на два
тижні протягом 2013—2015 років. На ділянках зафіксовано переривчасті зміни рівня питомої активності
¹³⁷C у всіх досліджених шарах ґрунтів протягом календарного року. Залежності вмісту ¹³⁷C у різних шарах ґрунту від сезону року не виявлено. Розрахунок коефіцієнтів кореляції свідчить про наявність
взаємозв’язку між коливаннями концентрації радіоцезію лише між шарами 0—5 та 5—10 см. Температура
повітря та опади протягом різних часових інтервалів, що передували відбору проб, не впливають на перерозподіл ¹³⁷C у ґрунті лісових екосистем. Висловлено припущення, що відсутність сезонних закономірностей зміни вмісту ¹³⁷C у ґрунтах пов’язана з його неоднорідністю (різною кількістю ґрунтової біоти в кожному зразку).